Efektifitas problem-based learning dengan pendekatan hybrid learning terhadap kemampuan pemecahan masalah matematis - Sutisna, Eki; Nindiasari, Hepsi (Tirtamath: Jurnal Penelitian dan Pengajaran Matematika, 2023)
The purpose of this study was to determine the effectiveness of the problem based learning method with hybrid learning approach through students' mathematical problem solving abilities. This research approach is a quantitative with the type of pre-experimental research designed, using the one group pretest posttest design technique. The research sample was students in one of the senior high schools in Tangerang, with the population was all students of class XII MIPA 1, its amount 24 students. The data analysis technique used descriptive and inferential analysis. The results showed that before the method was given to the students, the average problem-solving ability test results were 4.42 and after applying the method, the average problem-solving ability test results increased by 7.08, so that there was an average increase of 37%. It can be seen that the problem-based learning method with hybrid learning approach is quite effective on the ability to solve students’ mathematical problems.